2015
DOI: 10.1590/s2179-975x5914
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic features of a river from the Upper Tietê River Basin (SP, Brazil) along an environmental gradient

Abstract: Aim:This study aimed to assess the spatial and seasonal variation of the water quality and physical habitat characteristics along the upper-middle stretch of the Paraitinga River, a tributary of Tietê River, considering the potential influence of different riparian conditions along the stretch studied. Methods: Sixteen sites with different riparian vegetation, including native forest, secondary forest, pasture, and eucalyptus were sampled during the dry and rainy seasons of 2004/2005, before the damming of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The study by Esteves, Lôbo and Hilsdorf (2015) in a humid area in Brazil showed that the condition of the river is affected by land use within a sub-watershed. The average turbidity found in areas of native or secondary forest was 16.27 and 14.60 NTU, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Esteves, Lôbo and Hilsdorf (2015) in a humid area in Brazil showed that the condition of the river is affected by land use within a sub-watershed. The average turbidity found in areas of native or secondary forest was 16.27 and 14.60 NTU, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Tietê River, along its course, suffers various impacts such as pollution, loss of riparian vegetation, and presence of dams, built mainly for electrical energy generation (Smith et al 2014). These numerous consecutive dams create a group of reservoirs that receive and accumulate organic and inorganic matter from adjacent systems, with pulses of nutrients concentration in rainy seasons, probably due to runoff (Rodgher et al 2005, Smith et al 2014, Esteves et al 2015. The clutch size of Macrobrachium species is influenced by temporary environmental factors (Mashiko 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of DRP in C3 exceeded up to 10 times the limit of 0.02 mg L -1 . In the evaluation of spatial and temporal variation of water quality along the Paraitinga River, a tributary of the Tietê River at São Paulo State (Brazil), the highest concentrations of TP (of the order of 0.1 mg L -1 ) were observed in the rainy season at pasture regions (Esteves;Lôbo;Hilsdorf, 2015). However, in the present work, the year in which C3 and C4 were carried out (2014) presented an atypical and very dry climate (Figure 2).…”
Section: Physical and Chemical Variables: Spatial And Temporal Variabmentioning
confidence: 99%